Three-year safety and two-year effectiveness of etanercept in patients with rheumatoid arthritis in Japan: Results of long-term postmarketing surveillance. Issue 5 (3rd September 2019) - Yamanaka, Hisashi; Hirose, Tomohiro; Endo, Yutaka; Sugiyama, Noriko; Fukuma, Yuri; Morishima, Yosuke; Sugiyama, Naonobu; Yoshii, Noritoshi; Miyasaka, Nobuyuki; Koike, Takao
Abstract: Objectives: To evaluate the real-world safety and effectiveness of etanercept (ETN) in Japanese patients with rheumatoid arthritis. Methods: This postmarketing surveillance study (NCT00503139) assessed the safety and effectiveness of ETN treatment over 3 and 2 years (from June 2007 to September 2011), respectively. Safety was evaluated by occurrence and seriousness of adverse drug reactions (ADRs), and of adverse events (AEs) for malignancies. Effectiveness was assessed using the Disease Activity Score in 28 joints based on the erythrocyte sedimentation rate (ESR) with four variables (swollen and tender joint counts, ESR, and patient global assessment; DAS28-4/ESR). Treatment was considered effective if patients had a good/moderate response by the European League Against Rheumatism response criteria. Results: ADRs occurred in 256/675 (37.9%) patients, the most common being injection site reactions (4.4%) and nasopharyngitis (3.3%). Serious ADRs occurred in 60/675 (8.9%) patients, the most frequent being pneumonia (1.2%). The incident rate of malignancies (AEs) was 1.06 per 100 patient-years. Mean baseline DAS28-4/ESR for the 581 patients included in effectiveness analysis was 5.42, which decreased to 3.32 at 2 years. Eighty-two percent of patients achieved a moderate/good response at 2 years. Conclusion: Long-term ETN treatment safety and effectiveness were sustained over 3 and 2 years, respectively.